DOUBLE BURDEN OFMALNUTRITION IN SINGLETON PREGNANCIES AT A TERTIARY CARE TEACHING INSTITUTION IN NORTH KERALA, INDIA OUR EXPERIENCE - TRIVIKRAMA, HEERA SHENOY; KRISHNAN, REMASH; VK, CHELLAMMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This research was aimed at analyzing the dual burden of maternal pre-pregnancy body mass index (BMI) and their effects on the pregnancy outcomes in a tertiary care center in North Kerala. Methods: Based on maternal BMI calculated from the pregnant women’s height and pre-pregnancy weight, 299 pregnant women with singleton pregnancies were divided into four groups and morbidities compared. Results: Underweight women had two fold more chances of delivering an LBW infant. Maternal age in overweight or obese was slightly more and had longer operative time compared to those with normal weight. Maternal height and mean gestational age were comparable across the groups. Slightly heavier babies were born to mothers with increasing BMI. Mean hospital stay was 4.34–4.85 days in all the groups irrespective of body weight. Conclusion: The results re-iterated the existence of a double burden of malnutrition in rural mothers in Kozhikode district of North Kerala which can help policy makers the need to adopt appropriate pre-natal planning and counselling tailored to improve women’s nutritional status and thereby prevent possible adverse health outcomes in their reproductive career by achieving BMI to be between 18.5 and 22.9.